Factors associated with Toxoplasma gondii infection in confined farrow-to-finish pig herds in western France: an exploratory study in 60 herds. Issue 1 (December 2016) - Djokic, V.; Fablet, C.; Blaga, R.; Rose, N.; Perret, C.; Djurkovic-Djakovic, O.; Boireau, P.; Durand, B.
Abstract Background Infection byToxoplasma gondii postnatally can occur after ingestion of contaminated meat or water (tissue cysts/oocysts). In Europe, percentage of meat borne infections is estimated between 30 and 63 %, out of which pork makes the most important source. The aim of this study was to (i) investigate the seroprevalence ofT. gondii in intensive pig farms from western France; and (ii) identify the risk factors associated with seropositivity. Methods Data were collected between November 2006 and February 2008 in 60 intensive farrow-to-finish farms, where sera were taken from 3595 fattening pigs, weaned and suckling piglets. Information about three classes of potential seropositivity risk factors were obtained through a questionnaire concerning: (i) breeding characteristics; (ii) farm management; and (iii) husbandry and hygiene. The modified agglutination test (MAT) was used for detection of specific antiT. gondii antibodies in pig sera, starting from 1/6 dilution. Results The overall proportion of seropositive animals was 6.9 %, but the proportion of herds with at least one positive pig was 100 %. Multivariate logistic mixed model showed an increased seropositivity risk in weaned compared to suckling piglets, and a decreasing risk for mid-sized and large farms. The presence of a Danish entry facility, that clearly separates clean and dirty areas, had a protective effect onT. gondii seropositivity as well. Conclusions The observed proportion of herds with at least oneT. gondii seropositive animal provides further evidence that even in confined conditions of pig breeding, infection occurs, and is common. The highest risk for acquiringT. gondii is at the end of weaning period. Smaller confined pig farms demonstrate higherT. gondii seropositivity levels. This study also showed that Danish entry on farm buildings provides effective protection againstT. gondii .